Phytosynthesis, Antimicrobial and Catalytic Activities of Silver Nanoparticles derived using Leaf and Stem Extracts of Indigofera macrophylla (2022)
Background: The phytosynthesis of metal nanoparticles is a promising green alternative to traditional chemical approaches. Objective: The aim of this study was to synthesize silver nanoparticles (AgNPs) with antimicrobial and biocatalytic activities using aqueous leaf and stem extracts of Indigofera macrophylla. Methods: Critical reaction variables for the biosynthesis of AgNPs were optimized using UV-vis spectroscopy before the biosynthesised AgNPs were characterized using various spectroscopic and microscopic techniques. The biological activities of the biogenic nanoparticles were then investigated with particular focus on their antimicrobial activity and biocatalytic efficiency in the degradation of methylene blue. Results: The surface plasmon resonance of silver nanoparticles biosynthesized using aqueous extracts of leaf (LEAgNPs) and stem (SE-AgNPs) of I. macrophylla occurred at 430 and 426 nm respectively. Scanning electron microscopy images of the nanoparticles showed highly aggregated polymorphs with mostly spherical shape. The particle sizes of LE-AgNPs and SE-AgNPs as determined by Transmission electron microscopy were 48.61±8.60 and 18.09±4.13 nm respectively with Energy dispersive X-ray analysis confirming characteristic absorption band at 3 KeV. In susceptibility assays, LE-AgNPs showed dose-dependent zones of inhibition against Escherichia coli (18mm), Staphylococcus aureus (18 mm), Pseudomonas aeruginosa (20 mm) while SE-AgNP was only active against Staphylococcus aureus (10 mm). Both LE-AgNPs and SE-AgNPs showed good biocatalytic efficiency in the degradation of methylene blue with rate constants of 0.0204 and 0.0182 min-1 respectively. Conclusion: Silver nanoparticles with antimicrobial and catalytic activities have been biosynthesized using the aqueous extract of Indigofera macrophylla.